Rare Case Report on Hydatid Cyst of Breast - Kassahun Tadele A; Israel Korga T; Melis Nisiro A; Abebe Ayele S (Dove Medical Press, 2022)
Abraham Kassahun Tadele,1 Tesfalem Israel Korga,2 Abebe Melis Nisiro,1 Selamawit Abebe Ayele1 1Department of Pathology, Hawassa University Comprehensive Specialized Hospital, Hawassa, Sidama, Ethiopia; 2Department of Pathology, Wolaita Sodo University Teaching Hospital, Wolayta, SNNP, EthiopiaCorrespondence: Abraham Kassahun Tadele, Tel +251910194890, Email Abrishk46@gmail.comAbstract: Hydatid cyst of the breast is a very rare disease that predominantly affects endemic regions. Breast hydatid cysts can occur alone or as a component of widespread hydatidosis. Histopathology is the best diagnostic method for hydatid cysts of the breast, but fine needle aspiration cytology can be utilized in preoperative diagnosis. Here we report, a case of a female patient who was diagnosed with Hydatid cyst of the breast Postoperatively in Wolaita Sodo University teaching hospital, southern Ethiopia. Preoperatively the patient was diagnosed with tuberculous mastitis and she took the full course of Anti Tuberculous treatment. After completing the treatment there was no improvement. The cyst was removed surgically and histopathology confirmed the disease to be Hydatid cyst of the breast.Keywords: hydatid cyst, benign breast lesion